286. THORACOPHRENOLAPAROMY FOR SURGICAL TREATMENT OF GEJ CANCER. (24th September 2022) - Garbarino, Giovanni Maria; Eshuis, Wietse J; Daams, Freek; van Berge Henegouwen, Mark I; Gisbertz, Suzanne S
Abstract: Nowadays, there is still a lack of consensus about the optimal surgical management of gastroesophageal junction (GEJ) tumor. The CARDIA-trial results, comparing transthoracic esophagectomy versus transhiatal extended gastrectomy for GEJ type II tumor, are still expected. Thoracophrenolaparotomy (TPL) allows to perform radical resections (higher rate of R0 and more extensive mediastinal lymphadenectomy) with both esophago-gastric or esophago-jejunal anastomoses. The aim of this study is to describe TPL for the treatment of GEJ and gastric cancer. A retrospective analysis of all TPL performed for GEJ and gastric cancer with esophageal involvement at the Amsterdam UMC from January 2019 to October 2021 was conducted. The primary endpoint was the evaluation of R1 resections. The secondary endpoints were postoperative and pathological outcomes. Forty-seven patients were included for the analysis. 18 patients underwent an esophago-cardia resection with gastric conduit reconstruction and 29 patients a total gastrectomy with distal esophagectomy. The main indications for TPL were cT3 (74.5%) and cN+ (55.3%) tumors. Postoperative pneumonia occurred in 4 (8.5%) patients and anastomotic leak in 2 (4.3%) patients. The mean hospital stay was 9.8 (±6.1) days. The mean tumor size was 42.3 (±32.8) mm and the mean proximal margin 31.0 (±20.7) mm. Two (4.3%)patients had a R1 resection of whom only one (2.1%) had a positive proximal margin. The mean number of retrieved lymph nodes was 31.6 (±9.9). Thoracophrenolaparotomy for selected patients with GEJ and gastric cancer is associated with high R0 resection rate, low pneumonia and anastomotic leak incidence, together with a short hospital stay. TPL should still be considered a reliable surgical option, even in high-volume centers for minimally invasive upper gastrointestinal surgery.